Feto-Maternal Crosstalk in the Development of the Circadian Clock System - Astiz, Mariana; Oster, Henrik (Frontiers in Neuroscience, 2021)
The circadian (24-hour) clock system adapts physiology and behavior to daily recurring changes in the environment. Compared to the extensive knowledge assembled over the last decades on the circadian system in adults, its regulation and function during development is still largely obscure. It has been shown that environmental factors, such as stress or alterations in photoperiod, disrupt maternal neuroendocrine homeostasis and program the offspring's circadian function. However, the process of circadian differentiation cannot be fully dependent on maternal rhythms alone, since circadian rhythms in offspring from mothers lacking a functional clock (due to SCN lesioning or genetic clock deletion) develop normally. This mini-review focuses on recent findings suggesting that the embryo/fetal molecular clock machinery is present and functional in several tissues early during gestation. It is entrained by maternal rhythmic signals crossing the placenta while itself controlling responsiveness to such external factors to certain times of the day. The elucidation of the molecular mechanisms through which maternal, placental and embryo/fetal clocks interact with each other, sense, integrate and coordinate signals from the early-life environment is improving our understanding of how the circadian system emerges during development and how it affects physiological resilience against external perturbations during this critical time period.